Further results on super edge-magic total labeling of extended w-trees - Javaid M.; Bhatti A.A.; Hussain M. (Utilitas Mathematica, 2016)
In 1970's Kotzig and Rosa conjectured that every tree is edge-magic. Enomoto et al. in 1980, proposed the conjecture that every tree is super edge-magic total. Javaid et. al [15,16,19] defined w-tree and extended w-tree. They proved some results related to super edge-magic total labeling of w-trees and extended w-trees. In this paper we prove some more results related to super edge-magic total labeling on extended w-trees, isomorphic and non-isomorphic copies of extended w-trees.